Hospital's ReDOWSKo Application Forms and Influence in Action - Eni, Yuli; Layman, Chrisanty (Milestone: Journal of Strategic Management, 2021)
The rise of the current digital era brought by further sophisticated technology increases access to global information and advancement in various industry application. In 2012, Hospital Accreditation Commission KARS launched an application to assist hospitals in accreditation assessment. Due to the lack of understanding and perception of accreditation standards, improvements were made to develop new standards using a methodology called ReDOWSKo. This study will look into measuring the use between ReDOWSKo application and book form. Data was collected using google form questionnaire and analyzed using descriptive statistic and correlation method. The results show there is a relationship between the ReDOWSKo assessment in the form book and application with the nature of weak and unidirectional relationships. In this case the application is used to help remember important elements in accreditation. There is also correlation that is statistically significant between application users and book users and there is a positive relationship between the use of ReDOWSKo book form with application form. This application relatively new, and have little literature found while the use of the ReDOWSKo application is indeed considered not yet optimal. This study suggest it would require time for adoption of the use of the application that could enhance the effectiveness of ReDOWSKo. Therefore, will include upgrading the application and further socialization and training in the upcoming years.